PERAN RHIZOBAKTERI DALAM FITOSTABILISASI LOGAM BERAT KROMIUM - , Ali Pramono, SP. ([Yogyakarta] : Universitas Gadjah Mada, 2011)
The widespread use of industrial heavy metal has to be considered as a serious environmental pollutant. A high concentration of heavy metal can be absorbed and accumulated by organisms and disturbed their metabolism. Chromium is one of the heavy metal that can be carcinogenic. In nature, chromium can be the third valence [Cr(III)] and sixth valence [Cr(VI)] forms. Cr(VI) is more toxic than Cr(III) due to their high solubility and mobility in nature. When the chromium gets into cell may cause DNA disturbances which lead to mutation. While Cr(III) is less solubility and very important for metabolism such as insulin co-factor. Based on the toxic character of Cr(VI), it is a must to remediate the chromium polluted environment. One of the remediation technologies uses living organisms such as microorganisms, because they have ability to reduce Cr(VI) into Cr(III). The aims of this research were to evaluate the reduction activity of rizhobacterial isolates and to identify these rhizobacteria which take a role in reducing chromium absorption by plant. The isolates were tested for resistance and reduction of Cr(VI). Resistance test was conducted by growing the bacteria on the LB agar medium supplemented with 6-600 ppm Cr(VI). The reduction test was conducted by growing cells, resting cells and supernatant of the bacteria in medium containing 15 ppm Cr(VI). The Cr(VI) concentration in medium was measured by colorimetric method. Bacterial growth was observed by turbidity method. The bacterial isolates that resist and have ability to reduce Cr(VI) were identified. This research results showed that solate 3 and isolate 39 were able to grow on LB medium containing 300 and 200 ppm Cr(VI), respectively. Since LB medium could reduce Cr(VI) due to organic components, this research used minimal medium to minimize the reduction by media. Isolate 3 and isolate 39 reduced Cr(VI) up to 15 ppm concentration level in minimal medium. Isolate 3 and isolate 39 have ability to reduce Cr(VI) at growing cells and resting cells conditions. Isolate 3 and isolate 39 could reduce Cr(VI) up to 92.00 and 94.89% on growing cells within 12 hours, respectively. By resting cells, isolate 3 and isolate 39 were able to reduce up to 29.11 and 30.89% of Cr(VI) within 12 hours, respectively. Cr(VI) reduction by these isolates is derived from extracellular enzyme activity using organic acids as electron donor. Isolate 3 and isolate 39 increased the phytostabilization ability of chromium by Zea mays at 30 days after seeding 1.9 and 3.5 times compared than control (without isolate), respectively. Based on partial sequencing of 16S rRNA gene, isolate 3 was identified as Agrobacterium sp.